2018
DOI: 10.1016/j.dcn.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The error-related negativity (ERN) is an electrophysiological marker of motor impulsiveness on the Barratt Impulsiveness Scale (BIS-11) during adolescence

Abstract: These findings provide preliminary evidence that ERN amplitude is an electrophysiological marker of self-reported motor impulsiveness (i.e. acting without thinking) during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 75 publications
1
16
1
Order By: Relevance
“…This contrasts to what has been found in the larger literature on the development of the ERN, an ERP with a neural origin and timing similar to the N2 (Gruendler et al, 2011;Van Noordt, Campopiano, & Segalowitz, 2016). The ERN seems to show continued development through adolescence (Davies, Segalowitz, & Gavin, 2004a, 2004bLadouceur, Dahl, & Carter, 2004;Santesso & Segalowitz, 2008;Santesso, Segalowitz, & Schmidt, 2006;Taylor, Visser, Fueggle, Bellgrove, & Fox, 2018). This is also what we found in the sample of the present study (Overbye et al, 2019).…”
Section: Relationships Between Age and Electrophysiological Componentscontrasting
confidence: 99%
“…This contrasts to what has been found in the larger literature on the development of the ERN, an ERP with a neural origin and timing similar to the N2 (Gruendler et al, 2011;Van Noordt, Campopiano, & Segalowitz, 2016). The ERN seems to show continued development through adolescence (Davies, Segalowitz, & Gavin, 2004a, 2004bLadouceur, Dahl, & Carter, 2004;Santesso & Segalowitz, 2008;Santesso, Segalowitz, & Schmidt, 2006;Taylor, Visser, Fueggle, Bellgrove, & Fox, 2018). This is also what we found in the sample of the present study (Overbye et al, 2019).…”
Section: Relationships Between Age and Electrophysiological Componentscontrasting
confidence: 99%
“…It is worth noting that a largely overlapping pattern of results that indicates reduced ERN amplitudes was found in individuals with a tendency toward impulsive responding (Pailing, Segalowitz, Dywan, & Davies, ; Ruchsow et al, ; Stahl & Gibbons, ) or with high self‐reported impulsivity (Martin & Potts, ; Potts, George, Martin, & Barratt, ; Taylor, Visser, Fueggle, Bellgrove, & Fox, ). Thus, taken together with the previous findings, the present data support the assumption that both decisiveness and impulsivity may represent a maladaptive extreme of decision making that is linked to low response control and reduced error monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…B. Taylor et al, 2018). There are, however, also studies that have found no relationship between ERN amplitude and age during this developmental period (Eppinger et al, 2009;Richardson et al, 2011).…”
Section: Introductionmentioning
confidence: 90%